Proceedings 2019 Workshop on Usable Security 2019
DOI: 10.14722/usec.2019.23008
|View full text |Cite
|
Sign up to set email alerts
|

In Control with no Control: Perceptions and Reality of Windows 10 Home Edition Update Features

Abstract: Home computer users are regularly advised to install software updates to stay secure. Windows 10 Home edition is unique as it automatically downloads and installs updates, and restarts the computer automatically if needed. The automatic restarts can be influenced through a number of features, such as 'active hours' (the period during which a computer will never automatically restart to finish installing an update) or by explicitly setting a time when to restart the computer. This research investigates if the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For the directionality of this relationship, there is only sparse evidence in the context of research on digital stress, with Shu, Tu, and Wang (2011) highlighting that these two stressors often accompany each other when new systems are introduced but they do not discuss whether the perception of these stressors could influence each other. We find some evidence for a potential directionality in a recent survey by Morris, Becker, and Parkin (2019) though, who found that the process of changing a system causes uncertainty, particularly as users are expecting problems with their device if an update takes place.…”
Section: Hypothesis Developmentmentioning
confidence: 64%
“…For the directionality of this relationship, there is only sparse evidence in the context of research on digital stress, with Shu, Tu, and Wang (2011) highlighting that these two stressors often accompany each other when new systems are introduced but they do not discuss whether the perception of these stressors could influence each other. We find some evidence for a potential directionality in a recent survey by Morris, Becker, and Parkin (2019) though, who found that the process of changing a system causes uncertainty, particularly as users are expecting problems with their device if an update takes place.…”
Section: Hypothesis Developmentmentioning
confidence: 64%
“…This moves in the direction of better matching updates to the work context, i.e., how operating system updates interact with corporate applications and systems, and how updates can fit into the work day of employees. This would be akin to knowing employees' 'Active Hours' (as is already seen within Windows 10 home installations [66]), and assessing whether these hours make it feasible to install the updates within the working day.…”
Section: Processmentioning
confidence: 99%
“…Rational advice to keep a system up-to-date does not consider that modern systems may already be doing (some or all of) this without user involvement, so advice may, for example, need to consider specific operating system software. Unless an operating system or application provides separate feature updates and security updates, the value of updates for security may not allow a decision-maker to consider clear choices [66]. A bounded security decision-making approach would acknowledge how updates work on the system the decision-maker is using.…”
Section: Available Policy Choicesmentioning
confidence: 99%